Drug detection tests and the important factors and effects of the development of addiction - Khaled Khader Z. Alatawi; Khalid Saleh D. Albalawi; Abdulrhman Abdulaziz M. Aljuhani; Nader Salem D. Albalawi; Adel Ibrahim Alalawy; Atif Abdulwahab A. Oyouni (Journal of King Saud University: Science, 2022)
Drug addiction is a serious issue. A lot of psychopathic drugs are in use, but mainly methamphetamine. Addiction is a problem not only for the addicted person but also affected family and the entire society. Addicted persons lose control of their actions and so commit different crimes such as stealing, raping and killing. They may end up committing suicide. In this review article, we analyze the causes of addiction, absorption of methamphetamine into the body, its effects on cells and the analytical tool to detect the chemicals.